Biogenesis and molecular characteristics of serum hepatitis B virus RNA - Shen, Sheng; Xie, Zhanglian; Cai, Dawei; Yu, Xiaoyang; Zhang, Hu; Kim, Elena S.; Zhou, Bin; Hou, Jinlin; Zhang, Xiaoyong; Huang, Qi; Sun, Jian; Guo, Haitao (PLoS pathogens, 2020)
HBV is an enveloped DNA virus that replicates its DNA genome via reverse transcription of a pregenomic (pg) RNA intermediate in hepatocytes. Interestingly, HBV RNA can be detected in virus-like particles in chronic hepatitis B (CHB) patient serum and has been utilized as a biomarker for intrahepatic cccDNA activity in treated patients. However, the biogenesis and molecular characteristics of serum HBV RNA remain to be fully defined. In this study, we found that the encapsidated serum HBV RNA predominately consists of pgRNA, which are detergent- and ribonuclease-resistant. Through blocking HBV DNA replication without affecting pgRNA encapsidation by using the priming-defective HBV mutant Y63D or 3TC treatment, we demonstrated that the cell culture supernatant contains a large amount of pgRNA-containing nonenveloped capsids and a minor population of pgRNA-containing virions. The formation of pgRNA-virion requires both capsid assembly and viral envelope proteins, which can be inhibited by capsid assembly modulators and an envelope-knockout mutant, respectively. Furthermore, the pgRNA-virion utilizes the multivesicular body pathway for egress, in a similar way as DNA-virion morphogenesis. Northern blotting, RT-PCR, and 3' RACE assays revealed that serum/supernatant HBV pgRNA are mainly spliced and devoid of the 3'-terminal sequences. Furthermore, pgRNA-virion collected from cells treated with a reversible HBV priming inhibitor L-FMAU was unable to establish infection in HepG2-NTCP cells. In summary, serum HBV RNA is secreted in noninfectious virion-like particle as spliced and poly(A)-free pgRNA. Our study will shed light on the molecular biology of serum HBV RNA in HBV life cycle, and aid the development of serum HBV RNA as a novel biomarker for CHB diagnosis and treatment prognosis.